2017
DOI: 10.5114/pjp.2017.71534
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral heterogeneity for inactivating frameshift mutation of CUX1 and SIRT1 genes in gastric and colorectal cancers

Abstract: *These two authors contributed equally to this work.Both CUX1 and SIRT1 are considered tumor suppressor genes (TSGs), but it is not known whether CUX1 and SIRT1 alterations are different between high microsatellite instability (MSI-H) and microsatellite stable MSI (MSS) cancers. We identified frameshift mutations of CUX1 in 4 cases of colorectal cancer (CRC) and of SIRT1 in 1 case of gastric cancer (GC) and 3 cases of CRC. All of them were found in GC or CRC with MSI-H (3.5% of MSI-H for each gene), but neithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Sirtuin 1 (SIRT1) is one of the early studied members of sirtuin family and is considered as a key regulator of various biological processes, especially in cancer. It has reported that SIRT1 is related to the tumorigenesis of gastric and colorectal cancers [2], the mitochondrial apoptosis of prostate cancer [3], and the prognosis of breast cancer [4]. Importantly, SIRT1 is confirmed to be involved in the tumorigenesis [5], proliferation [6], metastasis [7], and chemical resistant [8] of HCC which hinted its potential role in liver cancer.…”
Section: Introductionmentioning
confidence: 97%
“…Sirtuin 1 (SIRT1) is one of the early studied members of sirtuin family and is considered as a key regulator of various biological processes, especially in cancer. It has reported that SIRT1 is related to the tumorigenesis of gastric and colorectal cancers [2], the mitochondrial apoptosis of prostate cancer [3], and the prognosis of breast cancer [4]. Importantly, SIRT1 is confirmed to be involved in the tumorigenesis [5], proliferation [6], metastasis [7], and chemical resistant [8] of HCC which hinted its potential role in liver cancer.…”
Section: Introductionmentioning
confidence: 97%
“…CUX1 shares four similar DNA-binding domain architectures, including a CUT homeodomain and three CUT repeats (CR1, CR2, CR3), which are evolutionarily and functionally conserved from metazoans to humans (Ludlow et al, 1996;Vanden Heuvel et al, 2005;Kedinger et al, 2009). As a major member of the CUX family, it is involved in multiple biological processes including cell differentiation, proliferation, cell cycle regulation, tissue development, and double strand breaks (DSBs) repair response, besides, CUX1 expression was abnormally elevated in many malignant tumors and was implicated in tumorigenesis (Ramdzan and Nepveu, 2014;Wong et al, 2014;Jo et al, 2017). Many lines of evidence have indicated that overexpression of CUX1 was present in various types of cancers, such as melanoma, pancreatic cancer, multiple myeloma, and breast cancer (Fan et al, 2014;Vadnais et al, 2014;Krug et al, 2020).…”
Section: Introductionmentioning
confidence: 99%